Surgical treatment of a distal radius and ipsilateral metacarpal hemophilic pseudotumor without recurrence or functional deficit: a case report - Wang, Yingjie; Lv, Zehui; Dong, Xiying; Feng, Bin; Weng, Xisheng (Frontiers in Pediatrics, 2023)
Background: Distal hemophilic pseudotumor (HP) occurring distal to the wrist appear to be secondary to intraosseous hemorrhage, which develops rapidly and should be treated primarily with long-term replacement therapy and cast immobilization. Surgical removal or even amputation is indicated when conservative management fails to prevent progression. Here, a practical strategy was described for those patients who cannot afford the cost of routine coagulation factor replacement therapy, namely immediate surgical curettage and bone grafting as well as continuous follow-up. Case Description: A 7-year-old boy with a history of mild hemophilia A was admitted to our medical center because of a 2-year history of progressive swelling and pain around right forearm and hand. Coagulation factor VIII level was 11.1% of normal with no inhibitor. Radiographs revealed expansile swelling, bone destruction, and deformity of the distal right radius and the second metacarpal bone. He was diagnosed with distal HP. Surgical procedure of curettage and bone grafting was performed. The function and appearance of the right wrist were almost normal without discomfort at the 101-month follow-up. Significantly, the same patient was hospitalized again because of a year-long progressive swelling and pain around the left hand when he was 14 years old. X-ray showed multiple bone destruction of the left proximal phalanges of left thumb, middle finger and little finger with local pathological fractures. Surgical procedure of HPs including curettage and bone grafting was performed. Postoperative recovery was good, and the last clinical follow-up at 18 months after the operation displayed a satisfactory shape and functional outcomes. Conclusions: Curettage and bone grafting prove to be safe and feasible for patients with distal HP and continuous follow-up of patients with distal HP is very vital for timely finding and then treating successive HP in developing countries.